Protective effects of berbamine against arginase-1 deficiency-induced injury in human brain microvascular endothelial cells - Wei, Xiaolan; Li, Weiwei; Chen, Zixuan; Chen, Jintu; Chen, Yun; Cai, Jiangping; Lin, Huasong (Frontiers in Pharmacology, 2025)
Endothelial cell dysfunction plays a crucial role in the early development of cerebral small vessel disease (CSVD). Arginase-1 (ARG1) is expressed in endothelial cells, and its deficiency may exacerbate cerebrovascular damage by increasing reactive oxygen species (ROS) production, thereby inducing endothelial cell apoptosis. Berbamine (BBM) has shown potential in neuroprotection and cardiovascular disease prevention. This study aimed to investigate the impact of ARG1 deficiency on human brain microvascular endothelial cells and the protective effects of BBM against ARG1 deficiency-induced damage. Human brain microvascular endothelial cells (HCMEC/D3) were cultured in vitro, and ARG1 knockdown or overexpression was achieved using plasmid transfection techniques. We examined the effects of ARG1 expression levels on HCMEC/D3 cell viability, migration, apoptosis, adhesion, and angiogenesis through cellular experiments. Additionally, we explored how ARG1 expression levels influenced arginine (Arg), nitric oxide (NO), and ROS levels in HCMEC/D3 cells. The results demonstrated that ARG1 deficiency inhibited HCMEC/D3 cell viability, migration, adhesion, and angiogenesis, while promoting apoptosis and elevating Arg, NO, and ROS levels in HCMEC/D3 cells. Next, the effect of different BBM concentrations on HCMEC/D3 cell viability was assessed using the CCK-8 assay, revealing that BBM at a concentration of 5 µM had no significant impact on cell viability. Subsequently, after successfully knocking down ARG1 in HCMEC/D3 cells, the cells were treated with BBM. The results showed that BBM effectively mitigated the negative effects of ARG1 deficiency on HCMEC/D3 cell viability, migration, apoptosis, adhesion, and angiogenesis, while also reducing Arg, NO, inducible nitric oxide synthase (iNOS), and ROS levels in HCMEC/D3 cells. In conclusion, this study suggests that ARG1 deficiency may damage HCMEC/D3 cells by increasing Arg levels, leading to elevated NO and ROS levels. BBM may provide protection to ARG1-deficient HCMEC/D3 cells by reducing Arg, NO, iNOS, and ROS levels. These findings deepen our understanding of the pathogenesis of CSVD and provide a theoretical basis for the clinical application of BBM.